2014
DOI: 10.1371/journal.pone.0094297
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sequencing Method for Quantifying Background Abundances of Symbiodinium Types: Exploring the Rare Symbiodinium Biosphere in Reef-Building Corals

Abstract: The capacity of reef-building corals to associate with environmentally-appropriate types of endosymbionts from the dinoflagellate genus Symbiodinium contributes significantly to their success at local scales. Additionally, some corals are able to acclimatize to environmental perturbations by shuffling the relative proportions of different Symbiodinium types hosted. Understanding the dynamics of these symbioses requires a sensitive and quantitative method of Symbiodinium genotyping. Electrophoresis methods, sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 91 publications
3
133
1
Order By: Relevance
“…In fact, the diversity reported here is almost five times greater than that reported in other recent next-generation sequencing studies on Symbiodinium diversity (Quigley et al , 2014; Thomas et al , 2014; Arif et al , 2014; Green et al , 2014; Edmunds et al , 2014b). For example, a study on Acropora coral species (Thomas et al , 2014) at another high latitude reef (Abrolhos Island, Western Australia) found a Shannon diversity of 0.145 (vs 0.620 at LHI in September 2012).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In fact, the diversity reported here is almost five times greater than that reported in other recent next-generation sequencing studies on Symbiodinium diversity (Quigley et al , 2014; Thomas et al , 2014; Arif et al , 2014; Green et al , 2014; Edmunds et al , 2014b). For example, a study on Acropora coral species (Thomas et al , 2014) at another high latitude reef (Abrolhos Island, Western Australia) found a Shannon diversity of 0.145 (vs 0.620 at LHI in September 2012).…”
Section: Discussioncontrasting
confidence: 68%
“…Here, we challenge this notion by exploring the Symbiodinium rare biosphere using next-generation sequencing, a cost-effective, high-throughput method that has been recently shown to accurately detect low-abundance Symbiodinium types (Quigley et al , 2014; Thomas et al , 2014; Arif et al , 2014; Green et al , 2014; Edmunds et al , 2014b). We assess Symbiodinium communities in a time-series sample set to investigate (1) the cryptic diversity of the Symbiodinium rare biosphere within two common pocilloporid species; (2) possible changes within the Symbiodinium community over a period of time that spans two successive bleaching events; and (3) whether Symbiodinium shuffling and/or switching has occurred in pocilloporid corals from a subtropical reef at Lord Howe Island (LHI), eastern Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The generally greater diversity of Symbiodinium communities in early life-history stages compared to in adults 79 could be viewed as a bet-hedging strategy, providing juvenile corals with the opportunity to fine-tune endosymbiotic communities to suit ambient conditions. Finally, the retention of low-abundance background Symbiodinium types in adult stages of some corals 16,81 may provide further adaptive capacity to the holobiont (but see 82), facilitating future shuffling of dominant Symbiodinium types in response to changing environmental conditions 76,83 .…”
Section: Potential Involvement Of Microbes In Coral Acclimatizationmentioning
confidence: 99%
“…While their application to coral symbiont communities has only just begun, NGS approaches have the power to recover a more complete picture of community diversity, including the rare biosphere (Quigley et al, 2014), and require no prior taxonomic knowledge. However, while these approaches can estimate relative proportions of different symbiont types, these data are subject to numerous quantitative biases (Amend et al, 2010) and must still be normalized to surface area or other host parameters to quantify symbiont abundance.…”
Section: Measuring Symbiont Abundancementioning
confidence: 99%